(4x+1)-(6x-5)=

Simple and best practice solution for (4x+1)-(6x-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x+1)-(6x-5)= equation:


Simplifying
(4x + 1) + -1(6x + -5) = 0

Reorder the terms:
(1 + 4x) + -1(6x + -5) = 0

Remove parenthesis around (1 + 4x)
1 + 4x + -1(6x + -5) = 0

Reorder the terms:
1 + 4x + -1(-5 + 6x) = 0
1 + 4x + (-5 * -1 + 6x * -1) = 0
1 + 4x + (5 + -6x) = 0

Reorder the terms:
1 + 5 + 4x + -6x = 0

Combine like terms: 1 + 5 = 6
6 + 4x + -6x = 0

Combine like terms: 4x + -6x = -2x
6 + -2x = 0

Solving
6 + -2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -2x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + -2x = 0 + -6
-2x = 0 + -6

Combine like terms: 0 + -6 = -6
-2x = -6

Divide each side by '-2'.
x = 3

Simplifying
x = 3

See similar equations:

| 9s=8*36 | | 136=-8(1+3a) | | 8n-(5n+4)=14 | | 19s+60=31-s | | 5[4(2m+n+3)-6m-1]+2(5m-n)= | | -8y-(x-4x)+3= | | 3x-150=-39 | | -7(k+3)-4k=-109 | | 3(x-8)=2(x+3) | | 5a-16-8a=-10 | | 4x+1.18=-3.1(2-.01x) | | 2g+3(-8+3G)=1-g | | (-10)=6+4x-6x | | 31-(2c+4)=2(c+6)+c | | 722=485+b | | (5s-2t)-(2s-4t)= | | 7a=36*21 | | X+59+84+X+51=180 | | 128=-8(-2+2p) | | 42p-39=66p-87 | | 7-3d-5=-1+2d-12+d | | 247=-7(-1+8b)-4b | | a+25=-8 | | 3y-x=12 | | 7x+y=12 | | 4(x-4)+5=35-5x | | -14-2x=-4x+26 | | x-3/8=1/8 | | 2x+3=2(x-2) | | 138=n-216 | | 31-(2c+4)=2(c+6)c | | 5(2m+8)=100 |

Equations solver categories